EDUCATIONAL SERVICE MARKET AND THE PROSPECTS FOR THE DEVELOPMENT OF KNOWLEDGE IN GEORGIA - Chagelishvili-Agladze, Lali; Chagelishvili, Koba (European Scientific Journal, ESJ, 2014)
The rapid pace of globalization found its reflection in education sphere. Topic studies are in great progress in terms of education development and integration of knowledge. However, no serious researches are done. The same situation is evident in Georgia as well. Analysis in certain aspects of the educational service is made by Unified National Examination Center of the Ministry of Education and Science. But the work carried out by the center in this direction has more in formative nature than a complex scientific research. The paper analyzes the educational field, the most important aspects of marketing; on the base of problem analyzing and the cause-effective evaluation the author offers educational market service survey University model and sets the ways for knowledge development.